2008
DOI: 10.2319/022107-85.1
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of the Face in Orthodontic Patients

Abstract: Objective: To investigate the laterality of the normal asymmetry of the human face, examining differences in laterality in relation to sex, growth stage, and skeletal classification. Materials and Methods: A total of 1800 Japanese subjects (651 males and 1149 females; mean age, 15 years 3 months; range, 4 years 2 months to 59 years 11 months) were selected. Individuals in the sample were categorized according to sex, one of three growth stages, and one of three skeletal patterns. Differences in length between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
143
2
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(159 citation statements)
references
References 18 publications
5
143
2
9
Order By: Relevance
“…Numerous studies [26][27][28] have reported that the righthemiface tends to be wider than the left. The size difference between the right and left hemiface is suggested as one possible cause of the asymmetric displacements of the right and left corners of the mouth during voluntary smile.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies [26][27][28] have reported that the righthemiface tends to be wider than the left. The size difference between the right and left hemiface is suggested as one possible cause of the asymmetric displacements of the right and left corners of the mouth during voluntary smile.…”
Section: Discussionmentioning
confidence: 99%
“…Perfectly symmetric faces, constructed in computer software, are unnatural and are not as beautiful as the natural asymmetric ones [7]. It is known that a certain degree of asymmetry is beautiful, but the border line between normal asymmetry and asymmetry that requires treatment is subjective [8] and varies among professionals and lay people [6].…”
Section: Discussionmentioning
confidence: 99%
“…Any dental treatment during growth period might influence the downward and forward mandible growth potential. The displacement of the mandible towards the affected side such as asymmetric condylar growth could happen [2,3,7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the common craniofacial deformities is an asymmetric growth of the mandible or other diseases affecting the facial growth. It has a direct impact to aesthetic concern and functional problems of the stomatognathic system [1,2]. Factors potentially contributing to this individual masticatory action variation is related to the consistency of the diet and genetic predisposition that seems to be direct consequences of malfunction at the cellular level of condylar cartilage [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation